Effects Of Online Promotion And Personal Selling On The Purchase Decision Of The Cisauk Point Apartment During The Pandemic - Adinda Putri Astuti Ayu KUSUMA; Aldina SHIRATINA (Indonesia Strategic Sustainability, 2022)
The COVID-19 pandemic has affected all aspects of life. In the business sector, this COVID-19 pandemic forces millions of workers worldwide to work from home. Based on the phenomena and literature studies, the researcher wants to examine further the effect of online promotion and personal selling on perceived value as an intervening variable for the purchase decision of the Cisauk Point apartment during the pandemic. This study used descriptive quantitative research with a causal associative or explanatory method. This method is to determine the effect of independent variables (online promotion and personal selling) on ??the intervening variable (perceived value) and its impact on the dependent variable (purchase decisions). The population in this study was 182 consumers who purchased the Cisauk Point apartment during the pandemic from the beginning of 2020. The sampling was determined using a probability sampling of purposive sampling technique with predetermined criteria. Data were analyzed using SEM (structural equation marketing) with the help of the SmartPLS software. The results of this study showed that online promotion had a positive and significant influence on apartment purchase decisions during the pandemic and the perceived value variable acts as a partial mediating variable because with or without these variables, online promotion and personal selling still have a positive and significant effect on the decision to purchase the Cisauk Point apartment during the pandemic.